Problem solving with C++ : the object of programming. - Savitch, Walter, ....- (Boston : Addison-Wesley, 2003)
1.Introduction to computers and C++ programming 2.C++Basics 3.Procedural abstraction and functions that return a value 4.Functions for all suctasks 5.I/O streams as an introduction to objects and classes 6.Defining classes 7.More flow of control 8.Friends and overloaded operators 9.Separate compilation and namespaces 10.Arrays 11.Strings and vectors 12.Pointers and dynamic arrays 13.Recursion 14.Templates 15.Pointers and linked lists 16.Inheritance 17.Exception handling
Met index
Keywords: C (programmeertaal).; C++ (programmeertaal).